Analisis Dimensi Brand Trust Terhadap Brand Loyalty (Studi Pada Pengguna Simcard Im3 Mahasiswa Febis Unikarta ) - Sari, Nilam Anggar; Arifin, Dani (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract: The purposes of the study were analyzing the effect of dimensions of brand trust on brand loyalty both partially and simultaneously. Beside that, to find out the dominant variable in influencing brand loyalty. The analytical tool used was a factor analysis with 75 respondents. Based on the results where the KMO table and Barlettâ€™s test was obtained at 0.887 with a significant value less than 0.05(0,000 â‰¤ 0, 05). It can be concluded that the dimensions of brand trust have a significant and simultaneous influence on brand loyalty. The result also show the analysis of anti image correlation where each variable gives a contribution to the value of brand loyalty where each variables contributes: brand predictability (X1) 0,905; brand likings (X2) 0,895; brand competence (X3) 0,858; brand reputation (X4) 0,898 and trust in company (X5) 0,92. All these number above 0,5 and sig is far below 0.005 (0,000<0,000). It can be concluded that the dimensions of brand trust have a significant and partial influence on brand loyalty Based on the results of the component matrix analysis brand competence has the most dominant influence on the formation of brand loyalty IM3 brand with the highest correlation value 0,932. Keywords: Brand Trust, Brand Loyalty.